Tithe in the legislation of polish diocesan synods in XIII-XV centuries - Zarosa, Wojciech (Saeculum Christianum. Pismo Historyczne, 2021)
The issue of tithes was a very important aspect of the diocesan synods’ legislative activity. It is also argued that tithes had a great importance for ecclesiastical institutions’ functioning. The author makes an attempt to interpret and analyse the most important tithe statutes which were issued between XIIth and XVth century. The author focuses on the Archdiocese of Gniezno, diocese of Cracovia, diocese of Breslau, diocese of Plock and diocese of Poznan. These dioceses were responsible for customising the norms of the canon law to regional principle. Those were issued by legate and provincial synods. It is worth noting that diocesan synods reacted for new occurrences and processes having political, economic or social character. The regulation of the internal church’s web of tithes was one of the most important issues which the diocesan synods’ legislation had to deal with. The creation of new structures resulted in the progressive erosion of parish structures. By that time it was hard to decide who should receive the tithes. Diocesan synods, basing on the common norms, decided to give the tithe only to clergyman who provided priestly activity (cura animarum). It was also banned to receive decima vagas – unspecified tithes. The 14th century brought new trends of tithe payment. The nobility started to struggle with the priesthood having power and position in Poland, of which the best example and symbol was Cracovian Bishop – Zbigniew Oleśnicki (1423-1455). The indicated movement stood against tithes as well as made attempts to restrain the tithe obligations. The issue of tithes was a very important aspect of the diocesan synods’ legislative activity. It is also argument that tithes had a great importance for ecclesiastical institutions’ functioning.